Alexander Bryan Johnson, A Treatise on Language. Edited, with a Critical Essay on his Philosophy of Language, by David Rynin. University of California Press, Berkeley and Los Angeles, 1947, 443 págs. - Lida, Raimundo (El Colegio de México, 2017)
Se reseñó el libro: A Treatise on Language. Edited, with a Critical Essay on his Philosophy of Language by David Rynin.